If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14x+16=-12x-1
We move all terms to the left:
-14x+16-(-12x-1)=0
We get rid of parentheses
-14x+12x+1+16=0
We add all the numbers together, and all the variables
-2x+17=0
We move all terms containing x to the left, all other terms to the right
-2x=-17
x=-17/-2
x=8+1/2
| 6x-3=2+4x-11 | | 3k+3=5k-1 | | k−7=16 | | −63=14+7n | | 5x-17=3x+90-11 | | -11(v+3)=198 | | |5x|+8=43 | | 6(u-6)-9=-5(-5u+7)-3u | | (2u-7)=18 | | 23+n=389 | | -11v(v+3)=198 | | 16v=9v+14 | | x+4=7(x+4) | | 3(b+1)=4b1 | | 3(x+2)=-2 | | -2/3m-4=10= | | 0.3x+1.84=0.67 | | 5m-4=-109 | | 9v+24=-3(v+4) | | x²-3x=3x+16 | | 4(u-5)-6u=-18 | | -2/9u=8 | | t+25=57 | | -2(2d+5=10 | | 252-8x=12 | | 4+w/2=6 | | 5+3s/4=17 | | 2v-8=7v-35 | | -26=6(y-5)-8y | | 2(w+7)-6w=30 | | 5x+8=50-2x | | 1.75x=10 |